Cognitive-behavioral intervention in pediatric palliative care: a clinical case - Gómez Zarco, Alberto; Becerra Gálvez, Ana Leticia; Tron Álvarez, Rocio; Hernández Solís, Patricia (Psicooncología, 2018)
Objective: Childhood cancer is a disease that modifies the style and quality of life of children and their families due to the physical, emotional and financial impact it has on them. Pediatric Palliative Care has among its functions the granting of psychological attention to children and their families from the pre-diagnostic stage until terminal stage. We present the case of a pediatric patient diagnosed withSynovial Sarcoma who presents depression and anxious avoidance as a result of her medical condition.Method: The evaluation was carried out through a behavioral interview, direct observation of anxiety anddepression responses in the hospital and Visual Analogue Scale (VAS) for pain. The treatment consistedof seven sessions of intervention with Cognitive-Behavioral Therapy techniques. Results: The obtainedresults include adaptive verbalizations about their condition, possible medical treatments, self-concept, animprovement in emotional expression and management of pain. Conclusion: This case is a sample of theimportance of the work of the psychologist in Pediatric Palliative Care, as well as the impact of workingwith children suffering from oncological diseases and their families. Cognitive-Behavioral Therapy hasbeen shown to be highly effective in this type of patients, even in brief interventions.
Keywords: Pediatric palliative care; cognitive-behavioral therapy; pain; anxiety and depression